Komunikasi Lingkungan dalam Media Sosial Studi Bibliometrik Wacana Perubahan Iklim dan Keterlibatan Publik - Nailah Syakirah; Rully Khairul Anwar; Yunus Winoto (The Journal of Society and Media, 2025)
This study uses bibliometric analysis based on the Biblioshiny application in R Programming to explore climate change discourse in social media. Data were obtained from Scopus from 2008-2024, resulting in 57 scientific articles that were analyzed to explore research trends, lead author contributions, collaboration networks, information sources, and country of origin. The study provides an overview of the dataset, publication trends, citations, author profiles, journal analysis, country distribution, and research themes. Using a bibliometric approach, it aims to analyze the evolution of climate change discourse and enhance communication policies on social media. The results show a significant increase in publications each year, with a peak in 2024 High-impact articles by Koteyko N., Jaspal R., and Nerlich B. are key references. The U.S. and U.K. lead in publications and global scientific influence, while developing countries' contributions are lacking, emphasizing the need for international collaboration to enhance global representation in research. Key journals like Science Communication and Geographical Journal are vital for disseminating research on themes such as climate change, social media, and communication. Notable research areas include sentiment analysis, social networks, and environmental management, offering insights that can aid in developing inclusive and sustainable communication policies.